2022
DOI: 10.1111/bjc.12362
|View full text |Cite
|
Sign up to set email alerts
|

Unrealistic pessimism and obsessive‐compulsive symptoms during the COVID‐19 pandemic: Two longitudinal studies

Abstract: Objective Unrealistic pessimism (UP) is an aspect of overestimation of threat (OET) that has been associated with obsessive‐compulsive disorder/symptoms (OCD/OCS). During the COVID‐19 pandemic, UP may have played an important role in the course of OCD. To investigate the relationship, we conducted two longitudinal studies assuming that higher UP predicts an increase in OCS. Method In Study 1, we investigated UP in the general population ( N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…These participants were invited to participate in a second assessment 3 months later between June 22 and June 30, 2020 (t2), soon after the easing of the first lockdown restrictions in Germany. Findings from the data collected at the start of the pandemic (t1) and (t2) have been reported before, focusing on the course of OCS in the general population from t1 to t2 (Jelinek et al, 2021a) and the role of a cognitive bias (unrealistic pessimism) at the start of the pandemic (Jelinek et al, 2022). The focus of the current study was the long-term course of C-OCS.…”
Section: Recruitment and Proceduresmentioning
confidence: 81%
See 1 more Smart Citation
“…These participants were invited to participate in a second assessment 3 months later between June 22 and June 30, 2020 (t2), soon after the easing of the first lockdown restrictions in Germany. Findings from the data collected at the start of the pandemic (t1) and (t2) have been reported before, focusing on the course of OCS in the general population from t1 to t2 (Jelinek et al, 2021a) and the role of a cognitive bias (unrealistic pessimism) at the start of the pandemic (Jelinek et al, 2022). The focus of the current study was the long-term course of C-OCS.…”
Section: Recruitment and Proceduresmentioning
confidence: 81%
“…Models A1-A5 analyzed change in C-OCS over time (OCI-R washing subscale at t1 minus OCI-R washing subscale at t3) entered as the dependent variable. Demographic background variables (age, gender, education) were entered as the first block of predictors (model A1) and to control for regression to the mean (following previous publications; e.g., Jelinek et al, 2021bJelinek et al, , 2022 psychopathology at t1 (OCI-R washing subscale) as the second block of predictors (model A2). Changes in duration of handwashing over the first 3 months of the pandemic (i.e., t1-t2) were entered as the third block (model A3) and frequency of handwashing in the fourth block (A4).…”
Section: Discussionmentioning
confidence: 99%
“…22 Regarding OC symptomatology, some studies have indicated that OC symptoms tended to recede as the pandemic progressed. 23 On the contrary, other studies have indicated that OC symptomatology tended to increase despite the pandemic becoming milder. 3,24 With reference to QoL/well-being, a slight trend towards improvement was found in a study conducted in Austria six months after the outbreak of COVID-19.…”
Section: Introductionmentioning
confidence: 95%
“…One example of such health beliefs is the perception of the likelihood of contacting COVID-19 for a person compared to someone of the same age, sex, residency, and health status. Nevertheless, these results were obtained when some COVID-19-related demographic characteristics such as having vulnerable conditions (e.g., hypertension) were not considered, given the association between perceived vulnerability to COVID-19 and OCS ( 16 ).…”
mentioning
confidence: 94%
“…After reviewing several studies, the authors selected the most important demographic characteristics in the recent pandemic ( 19 , 30 ) (see demographic characteristics in Table 1 ). The authors anticipate that COVID-19-related demographic characteristics (e.g., having a vulnerable family member) ( 16 ) and certain health beliefs (e.g., perceived susceptibility and perceived severity) ( 14 ) will predict OCS changes more accurately than other variables. In other words, the present research pursues two goals: (a) examining the impact of having or not having COVID-19 patients in the family on OCS and health beliefs, and (b) predicting changes in outcomes through the health belief model.…”
mentioning
confidence: 99%